2002
DOI: 10.1016/s0925-4773(02)00241-1
|View full text |Cite
|
Sign up to set email alerts
|

A zebrafish orthologue (whnb) of the mouse nude gene is expressed in the epithelial compartment of the embryonic thymic rudiment

Abstract: The cloning and characterization of the zebrafish orthologue of the mouse nude (Whn/Foxn1) gene, whnb are reported. A previously described Whn-like gene from zebrafish, now designated as whna, is shown to be the orthologue of the mouse Foxn4 gene. The whnb gene is specifically expressed in the thymic rudiment of zebrafish embryos at day 3 after fertilization, whereas the whna gene is expressed in eye and brain structures. Whnb expression is maintained in cloche mutants, where endothelial and haematopoietic cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 20 publications
2
44
0
Order By: Relevance
“…3B), properly assembled tcrb genes are expressed and detectable by RT-PCR. The expression of foxn1, a characteristic marker for thymic epithelial cells (29,35), is unaffected, although foxn1-positive cells are less dispersed in the thymic rudiment as a result of the reduced number of hematopietic cells (Fig. 3C).…”
Section: Characterization Of the Il7r Mutantmentioning
confidence: 99%
“…3B), properly assembled tcrb genes are expressed and detectable by RT-PCR. The expression of foxn1, a characteristic marker for thymic epithelial cells (29,35), is unaffected, although foxn1-positive cells are less dispersed in the thymic rudiment as a result of the reduced number of hematopietic cells (Fig. 3C).…”
Section: Characterization Of the Il7r Mutantmentioning
confidence: 99%
“…7C-F). However, the expression of forkhead box N1 (foxn1) [36], a thymus epithelial marker, was indistinguishable between Ddx46 hi2137/ + and Ddx46 hi2137/hi2137 larvae (Fig. 7G, H), indicating that thymus formation is normal in these mutants.…”
Section: Ddx46mentioning
confidence: 99%
“…Although functional evidence is still lacking, it has been suggested that Foxn1 homologues in other vertebrates possess the same function. Indeed, a Foxn1 homologue, initially termed whnb and now called foxn1, was identified and shown to be expressed in the larval thymic anlage of zebrafish (3). It is currently unknown how Foxn1 expression is initiated in the prospective thymic anlage and which signal(s) maintain its expression.…”
Section: Maintenance Of Thymic Epithelial Phenotype Requires Extrinsimentioning
confidence: 99%